Progress toward resolving the attentional capture debate. Issue 1 (2nd January 2021) - Luck, Steven J.; Gaspelin, Nicholas; Folk, Charles L.; Remington, Roger W.; Theeuwes, Jan
ABSTRACT: For over 25 years, researchers have debated whether physically salient stimuli capture attention in an automatic manner, independent of the observer's goals, or whether the capture of attention depends on the match between a stimulus and the observer's task set. Recent evidence suggests an intermediate position in which salient stimuli automatically produce a priority signal, but the capture of attention can be prevented via an inhibitory mechanism that suppresses the salient stimulus. Here, proponents from multiple sides of the debate describe how their original views have changed in light of recent research, as well as remaining areas of disagreement. These perspectives highlight some emerging areas of consensus and provide new directions for future research on attentional capture.